Language and Gender in Short Films: I'm Just Your Clown: Sociolinguistic Study - Rosyidah, Neneng Aida (International Journal on Advanced Science, Education, and Religion, 2025)
The film I'm Just Your Clown is a short film on the Fikrifadlu YouTube channel about the story of the life of a teenage girl named Fia who is cheated on by her boyfriend and then tries to tell her complaints to her boyfriend Alwi. The use of language between female and male characters in this film is the focus of this research. The aim of this research is to describe the language differences between male and female characters and to describe the factors that influence the language differences between male and female characters. This research is a qualitative descriptive research. The data source in this research is the short film Aku Only Your Badut on the Fikrifadlu YouTube channel which was viewed and taken by watching the film from start to finish. Data collection was carried out by recording observations and then collecting them. The results of the research were to see the differences in language and characteristics of the male and female characters in this film.